Mouse Anaphylactic Hypotension Is Characterized by Initial Baroreflex Independent Renal Sympathoinhibition Followed by Sustained Renal Sympathoexcitation - Zhang, Tao; Tanida, Mamoru; Uchida, Kunitoshi; Suzuki, Yoshiro; Yang, Wei; Kuda, Yuhichi; Kurata, Yasutaka; Tominaga, Makoto; Shibamoto, Toshishige (Frontiers in Physiology, 2017)
Aim: The hemodynamic response to mouse systemic anaphylaxis is characterized by an initial hypertension followed by sustained hypotension. However, the defense mechanisms of the sympathetic nervous system against this circulatory disturbance is not known. Here, we investigated the renal sympathetic nerve activity (RSNA) response to mouse systemic anaphylaxis, along with the roles of carotid sinus baroreceptor, vagal nerves and the transient receptor potential vanilloid type 1 channel (TRPV1). Methods: Male ovalbumin-sensitized C57BL/6N mice were used under pentobarbital anesthesia. RSNA, systemic arterial pressure (SAP) and heart rate (HR) were continuously measured for 60 min after the antigen injection. Results: Within 3 min after antigen injection, RSNA decreased along with a transient increase in SAP. Thereafter, RSNA showed a progressive increase during sustained hypotension. In contrast, HR continuously increased. Sinoaortic denervation, but not vagotomy, significantly attenuated the renal sympathoexcitation and tachycardia from 30 and 46 min, respectively, after antigen. The responses of RSNA, SAP and HR to anaphylaxis were not affected by pretreatment with a TRPV1 inhibitor, capsazepine, or by genetic knockout of TRPV1. Conclusion: The mouse systemic anaphylaxis causes a biphasic RSNA response with an initial baroreflex-independent decrease and secondary increase. The antigen-induced sympathoexcitation and tachycardia at the late stage are partly mediated by carotid sinus baroreceptors. Either vagal nerve or TRPV1 does not play any significant roles in the RSNA and HR responses in anesthetized mice.